In Silico Evaluation of the Inhibition of Pseudomonas aeruginosa Biofilm Production in Burn Wound Infections Using CATH-2 and LL-37 Peptides - Priscilla Klaresza Adhiwijaya; Gabriella Zevania Kaitlyn; Louis Valenthenardo; Patricia Tiara Anjani; Mario Donald Bani (Indonesian Journal of Life Sciences, 2025)
Patients with burn injuries are at high risk of bacterial infection due to the loss of the skin barrier, often leading to complications that contribute to increasing death tolls from burn injuries. The formation of biofilms in bacteria increases its survival rate, especially in the rise of antibiotic resistance cases, which ineffectively combats biofilm production. This research explores the use of two types of cationic antimicrobial peptides, LL-37 and CATH2, commonly originating from humans and chickens, respectively, as a form of host defense in preventing the formation of biofilms by one of the most common pathogenic bacterial strains in severe burn wounds, Pseudomonas aeruginosa, through inhibition in its LPS region. In silico analyses were performed using AlphaFold, GLYCAM-Web, YASARA, and AutoDock Vina. It was found that the CATH-2 model has the strongest binding affinity towards the three types of LPS—alginate, Pel, and Psl—scoring between -5.5 and -6.0 kcal/mol, as opposed to the score range of -4.1 to -6.0 for LL-37. However, the LL-37 model is considered more precise than the CATH-2 model overall, meaning the in silico results of the former are likely more accurate in real life than the latter. These results suggest the utilization of the two peptides as treatments in severe burn cases. In future developments, the application of genetically engineered plasmid-inserted Staphylococcus epidermidis, a commensal bacterium commonly found on human skin, to produce peptides may be considered.